Clinical spectrum of primary cutaneous CD30-positive anaplastic large cell lymphoma: an analysis of the Mannheim Cutaneous Lymphoma Registry - Booken, Nina; Goerdt, Sergij; Klemke, Claus-Detlev (Journal der Deutschen Dermatologischen Gesellschaft, 2012)
Background: Primary cutaneous CD30+ anaplastic large cell lymphomas (C-ALCL) have indolent clinical behavior with an estimated 5-year survival rate of 95%. The clinical features and disease courses of C-ALCL identified in the lymphoma registry of Mannheim University hospital are described in the following. Patients and methods: All C-ALCL patients identified in the database were analyzed in regard to clinical picture, histology, immunohistochemistry, molecular biology, staging, therapy, follow-up, and outcome. Results: 14 C-ALCL patients were identified. The mean age was 69 years and 57% were men. Solitary skin lesions in one anatomical region were seen in 12 patients upon initial diagnosis. Two patients presented with multiple lesions at different anatomical sites. In 2 patients there was specific lymph node involvement. In one C-ALCL patient, follow-up over 17 months revealed extracutaneous infiltration. Half of the patients relapsed and 36% had multiple episodes. The majority of our patients were treated with surgical excision followed by electron beam radiotherapy. The 5-year survival rate was 93% in C-ALCL. Conclusions: The clinical presentation of C-ALCL varies. Staging procedures and a close clinical pathological correlation at initial diagnosis are essential. Due to a high rate of relapses and the possibility of developing extranodal manifestations over the course of the disease, close follow-up is recommended.